Moderation of novelty on experiences and enjoyment in national parks - Mkwizu, Kezia Herman (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2023)
The problem of low domestic tourists’ visitation to national parks still persists and this is a challenge. Therefore, the purpose of this paper was to examine the moderating effect of novelty on experiences and enjoyment of national parks. This paper specifically analyzed the moderating effect of novelty on direct experiences and enjoyment of southern national parks among domestic tourists guided by the types of tourists’ theory. This study was conducted in Nyerere National Park, Tanzania. Mixed methods approach is applied by adopting quantitative and qualitative to understand enjoyment in national parks. The quantitative approach provided the generalization of the findings while the qualitative findings supplemented the quantitative results. This study uses Partial Least Square Structural Equation Modelling (PLS-SEM) to analyze data collected from a survey sample size of 360 domestic tourists. Qualitative data is analyzed using content analysis. The findings indicate that there is a significant moderation effect of novelty on the relationship between direct experiences and enjoyment of southern national parks among domestic tourists. The practical implication is for the government and tourism stakeholders to consider improving communication and road connections to the park and other tourists’ facilities.